Solving initial-Value Problem of the First-Order Differential Equation by Euler’s Method using Casio fx 570EX Classwiz Scientific Calculator - Tay, K.G.; Cheong, T. H; Tiong, Wei King (International Journal of Trend in Scientific Research and Development - IJTSRD, 2018)
Solving numerical methods manually without using a scientific calculator or using scientific calculator traditionally without input the iterative formula into the calculator can be quite tedious and boring due to its repetitive calculations. There is a series of studies discussing the implementation of numerical methods using Excel spread sheet as well as Casio scientific calculators, such as Casio fx-570 MS scientific calculator, Casio fx-570 ES scientific calculator and Casio fx-570 ES plus scientific calculator. Even though Excel spreadsheet made the implementation of numerical methods easier to be understood by the learner of numerical methods, but it is not port classrooms (teaching and learning purposes) and examination hall (evaluation purpose). All the three mentioned models of scientific calculators allow the input of iterative formula but users still need to rein put the new inputs then press CALC bu iterative solutions. The new model of Casio fx FX classwiz scientific calculator offers a spreadsheet ability of 45 rows and 5 columns which made the implementation of the numerical methods much easier if compared to previous models. Hence, in this paper, we solved the initial-value problem (IVP) of the first order ordinary differential equations by the Euler’s method using Casio fx-570 FX class calculator for the classroom and examination purposes.